Ambulatory blood pressure and hypertension control in children with autosomal recessive polycystic kidney disease: clinical experience from two central European tertiary centres - Seeman, Tomáš; Blažík, Radek; Fencl, Fencl; Bláhová, Květa; Obeidová, Lena; Štekrová, Jitka; Weigel, Friederike; John-Kroegel, Ulrike (Journal of hypertension, 2022)
OBJECTIVE: : Arterial hypertension is a common complication in patients with autosomal recessive polycystic kidney disease (ARPKD), occurring in 33-75% of children when measured by office blood pressure (OBP). Ambulatory blood pressure monitoring (ABPM) is a superior tool for investigating blood pressure relative to OBP. The aim of our study was to investigate the prevalence and control of hypertension in children with ARPKD based on ABPM. METHODS: This retrospective study evaluated 36 children with ARPKD and at least one ABPM performed in two our tertiary paediatric nephrology centres and 29 children with at least two ABPM. Ambulatory hypertension was defined as mean daytime or night-time BP at least 95th percentile or use of antihypertensives and controlled hypertension as normal ambulatory BP in children on antihypertensive drugs. RESULTS: The first ABPM study revealed ambulatory hypertension in 94% of children. Untreated or uncontrolled ambulatory hypertension was diagnosed in 67% and controlled hypertension in only 28%. Masked hypertension was found in 5.5% and white-coat hypertension in 14%. The last ABPM study revealed ambulatory hypertension in 86% (all 86% hypertensive children on drugs, i.e. no untreated hypertension), the prevalence of controlled hypertension increased to 59%. Masked hypertension was detected in 8.3% and white-coat hypertension in 10%. Ambulatory blood pressure correlated neither with kidney length nor with glomerular filtration rate. Echocardiography demonstrated left ventricular hypertrophy (LVH) in 27% of children at the time of their first ABPM. CONCLUSION: The prevalence of ambulatory hypertension is very high in children with ARPKD, while the control of hypertension improves over time.
Keywords: ambulantní monitorování krevního tlaku; polycystické ledviny autozomálně recesivní; Blood Pressure; retrospektivní studie; Humans; Polycystic Kidney, Autosomal Recessive; krevní tlak; Retrospective Studies; Blood Pressure Monitoring, Ambulatory; Child; Hypertension; dítě; lidé; hypertenze